A Novel Class of Plant Type III Polyketide Synthase Involved in Orsellinic Acid Biosynthesis from Rhododendron dauricum - Taura, Futoshi; Iijima, Miu; Yamanaka, Eriko; Takahashi, Hironobu; Kenmoku, Hiromichi; Saeki, Haruna; Morimoto, Satoshi; Asakawa, Yoshinori; Kurosaki, Fumiya; Morita, Hiroyuki (Frontiers in Plant Science, 2016)
Rhododendron dauricum L. produces daurichromenic acid, the anti-HIV meroterpenoid consisting of sesquiterpene and orsellinic acid (OSA) moieties. To characterize the enzyme responsible for OSA biosynthesis, a cDNA encoding a novel polyketide synthase (PKS), orcinol synthase (ORS), was cloned from young leaves of R. dauricum. The primary structure of ORS shared relatively low identities to those of PKSs from other plants, and the active site of ORS had a unique amino acid composition. The bacterially expressed, recombinant ORS accepted acetyl-CoA as the preferable starter substrate, and produced orcinol as the major reaction product, along with four minor products including OSA. The ORS identified in this study is the first plant PKS that generates acetate-derived aromatic tetraketides, such as orcinol and OSA. Interestingly, OSA production was clearly enhanced in the presence of Cannabis sativa olivetolic acid cyclase, suggesting that the ORS is involved in OSA biosynthesis together with an unidentified cyclase in R. dauricum.